Handbook of antimicrobial resistance - Gotte, Matthias; Berghuis, Albert; Matlashewski, Greg; Wainberg, Mark A.; Sheppard, Donald (Springer, 2017)
"This is a comprehensive tool covering all manifestations of antimicrobial resistance, with viral, bacterial, parasitical and fungal resistance each given a dedicated section. The underlining molecular mechanisms, which depend not only on the microbe, but on the specific drug (target), are highly diverse, and are covered in great detail. This work also discusses and compares the biological, biochemical and structural aspects of resistance and its evolution"- Resumé vydavatel
Keywords: rezistence vůči antimikrobiálním látkám; lékařská mikrobiologie; imunologie; virologie; antimicrobial resistance; medical microbiology; immunology; virology; elektronické knihy; sborníky; příručky; electronic books; papers of several authors; handbooks and manuals